PENGARUH INFORMASI AKUNTANSI DAN IPO UNDERPRICING TERHADAP NILAI PERUSAHAAN - KUKUH BUDIANTO (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2020)
This study aims to obtain empirical evidence of the effect of Accounting Information and IPO Underpricing on Firm Value in companies listed on the Indonesia Stock Exchange in 2008 - 2017. Population & sample in this study were all companies that conducted Initial Public Offering (IPO) and listed on the Indonesia Stock Exchange from 2008 to 2017 with 3 year intervals totaling 105 companies. The population that meets the criteria to be sampled is 70 companies. The research method used in this study is using the Warp-PLS. The results showed that the effect of (1) Accounting Information on Firm Value is positive and significant (2) IPO Underpricing on Firm Value is negative and significant.